2017
DOI: 10.12820/rbafs.v.22n2p155-164
|View full text |Cite
|
Sign up to set email alerts
|

Perception of square and park characteristics and physical activity practice among High School students

Abstract: This study aimed to investigate the association between perception of the characteristics of square/parks (infrastructure, conservation, esthetics, safety, distance from residence, and access) and physical activity among high school students from the public network. It is a cross-sectional study with a quantitative approach and a random sample of 168 adolescents (40.3% male adolescents), 14 to 18 years of age, from the city of Passo Fundo, RS, Brazil. Perception of square/park characteristics was assessed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, inconsistent results persist. While Mendonça et al 12 showed that adolescents from João Pessoa who perceived that the neighborhood environment was not violent were more likely to report active commuting, other national studies have not found an association between urban violence and adolescent physical activity [23][24][25] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, inconsistent results persist. While Mendonça et al 12 showed that adolescents from João Pessoa who perceived that the neighborhood environment was not violent were more likely to report active commuting, other national studies have not found an association between urban violence and adolescent physical activity [23][24][25] .…”
Section: Discussionmentioning
confidence: 98%
“…However, it is observed from systematic reviews that evidence is still needed to help understand the relationship between physical activity in adolescents and the natural, built, and social environment, especially in low-and middle-income countries 5,17,18,21,22 . Precisely in Brazil, the scientific production that addresses the topic consists of studies with local samples, the vast majority evaluating the physical activity associated with the perceived environment, with results that are still not consistent 12,15,[23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the distance from open spaces was associated with leisure physical activity of girls in Argentine 29 . In Brazil, specifically in the southern region, the shortest distance to public squares/parks, beaches, and leisure facilities was positively associated with general physical activities practice, as well as moderate and vigorous physical activity during leisure [30][31][32] . We emphasize the relevance of our findings since walking/running track was related to walking, running, team sports, and other general physical activities.…”
Section: Discussionmentioning
confidence: 99%